Red Biocentrism for the Anthropocene. (15th November 2019) - Boxley, Simon
Abstract: If the dawn of the Anthropocene heralds the collapse of the natural and social sciences into a single geostory, then why not also a radical synthesis of the anthropocentrism of Marxist theorising with the biocentrism of Deep Ecology? This article proposes just such a unification for theorising education. First, those on the educational left who wish to develop a fundamental unity between red and green should perhaps unearth the roots of Deep Ecological thinking and delve into the long and manifold history of socialist movements, with the aim of identifying where, between the deep red and deep green, might lie some shared origins in common ground. The flawed but nevertheless distinctive monism of the first philosopher of Marxism, Joseph Dietzgen, offers a philosophy that both prefigures the cosmology of Deep Ecology and suggests means of reconciling the narrative of human toil and 'progress' with that of human 'nestedness'. The task facing the socialist looking to explore such a possibility needs to be located principally at the level of 'cosmic', rather than 'social' ontology, and this article sketches the outlines of such a unity project. Second, from this synthesis flows a set of implications for education and human growth. As the article explains, themes such as alienation and subjectification that cross-pollinate the theoretical perspectives might serve as central motifs in a red biocentric educational project fit for the Anthropocene. It is not solely environmental education, but approaches to education more broadly that require reconceptualisation for the Anthropocene.